The EFFECTIVENESS OF ARCADE GAMES IN IMPROVING THE UNDERSTANDING OF POETIC FIGURATIVE SPEECH - Sar, Siswantia; Payana, Wita Dwi (ELTIN Journal, 2025)
This study explores the effectiveness of arcade games in improving high school students' understanding of figurative speech and examines students' perceptions of using arcade games as a learning tool. The study presents a novel and captivating strategy to enhance students' literary comprehension, particularly in the use of figurative speech at the high school level. Using a mixed method of quantitative and qualitative approach, four selected student groups from two different schools were studied. The experimental group participated in sessions incorporating arcade games designed to teach figurative speech, while the control group followed traditional learning methods. Data was collected through pre- and post-intervention tests measuring students' understanding, along with a questionnaire evaluating their perceptions of arcade games as a learning tool. Statistical analysis was used to compare the differences in understanding between the two groups, providing knowledge into the effectiveness of arcade games in improving students' comprehension of figurative speech. The main finding from this research is that the use of arcade games significantly improves high school students' understanding of figurative speech and the students’ response toward the arcade game is mostly positive. The results suggest that arcade games can be a more effective and engaging method for teaching figurative speech compared to conventional approaches​.